PENINGKATAN PEMAHAMAN JILBAB DAN KONSTRUKSI KESALEHAN PERSONAL DAN SOSIAL DI MASJID USWATUN HASANAH SUKAHATI CIBINONG KABUPATEN BOGOR - Nur Arfiyah Febriani; Nurkhafifah Tamsyur; Akhmad Shunhaji; Tholhah Tholhah; Kholilurrohman Kholilurrohman (MADANI Abdimas : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
This article examines the concept of piety in Islam comprehensively by positioning the jilbab as one of the symbols situated between personal dimensions and social demands. In Islam, piety is not merely understood as individual ritual practices such as prayer, fasting, zakat, and pilgrimage, but also encompasses social, biological, aesthetic (appearance-related), and spiritual dimensions of piety. Grounded in the principle of tawhid as its primary foundation, this study affirms that piety represents an integration between the vertical relationship (ḥablum minallāh) and the horizontal relationship (ḥablum minannās). Within this framework, the jilbab is not solely perceived as a normative obligation or a symbol of religious identity, but also as a social construct rich in historical, cultural, and ideological meanings. Historically, the practice of head covering was known in various ancient civilizations prior to Islam, and was later adopted and reconstructed within the ethical and spiritual framework of Islamic teachings. From the perspective of symbolic interactionism, the jilbab functions as a medium of social communication that both shapes and is shaped by the collective meanings within society. In Indonesia, the dynamics surrounding the use of the jilbab demonstrate a shift in meaning—from merely a symbol of ritual piety to a marker of social identity, lifestyle, and even cultural expression. Nevertheless, reducing piety to its symbolic aspects risks creating an imbalance between outward (external) and inward (spiritual) piety. Through a descriptive-analytical approach supported by Islamic literature review and historical-sociological analysis, this article concludes that authentic piety is holistic in nature, integrating ritual, social, biological, aesthetic, and spiritual dimensions in a balanced manner. As a representation of piety, the jilbab should not be confined to an external symbol, but should instead manifest spiritual consciousness, moral integrity, and social responsibility in communal life